Asymmetric Supercapacitor Based on Nanostructured Ce‐doped NiO (Ce:NiO) as Positive and Reduced Graphene Oxide (rGO) as Negative Electrode. Issue 13 (16th August 2016) - Gawali, Swati R.; Dubal, Deepak P.; Deonikar, Virendrakumar G.; Patil, Santosh S.; Patil, Seema D.; Gomez‐Romero, Pedro; Patil, Deepak R.; Pant, Jayashree
Abstract: Asymmetric supercapacitor was fabricated successfully using cerium (Ce) doped NiO as positive electrode and reduced graphene oxide (rGO) as negative electrode in aqueous KOH electrolyte. Initially, Ce doped nickel oxide nanostructures were synthesized by simple Sol‐Gel method. To investigate the effect of Ce doping in nickel oxide, different molar percentages of cerium with respect to nickel were incorporated. Among the different compositions, 1%Ce:NiO exhibits high specific capacitance and excellent electrochemical activities. Further, asymmetric supercapacitor based on 1%Ce:NiO and rGO was fabricated which could be cycled reversibly in the high‐voltage range of 0 to 1.4 V and displays intriguing performances with a specific capacitance of 110 F/g at a scan rate of 5 mV/s with a maximum energy density of 26.27 Wh/kg (based on the total mass of active materials, 0.78 mg). Importantly, this asymmetric device exhibits an excellent electrochemical stability of 91.6 % over 1000 cycles. Abstract : Asymmetric supercapacitor has been fabricated using Ce doped NiO as positive electrode and reduced graphene oxide (rGO) as negative electrode. The asymmetric cell exhibits high‐potential window of 1.4 V with maximum energy density of 26.27 Wh/kg and excellent electrochemical stability of 91.6 % over 1000 cycles.